Banjarese: Self-Concept, Identity and River Culture - Abdurrahman, Abdurrahman; Abduh, Muhammad (Khatulistiwa, 2019)
Self-concept is the core of individual personality, which plays a role in determining and directing individual behavior. Self-concept cannot be separated from virtuous values that arise from self-identity. This article discusses the philosophy of life and the cultural values of the Banjar people "baiman, bauntung, batuah" which are used to conceptualize themselves. The values obtained from the strong influence of Islamic teachings on the Banjar people. The dominance of Islam in the Banjar community is undoubtedly, in the process of 'becoming a Banjar', many Dayak ethnic groups are 'becoming Banjars when they convert to Islam. In addition to this article discussing one of the unique cultural forms of Banjar people, the culture of the river, in the form of river transportation, pasar terapung, and rumah lanting, has begun to be neglected.